Pemberdayaan UMKM Desa Galengdowo melalui Pelatihan Desain Kemasan Produk dalam rangka Mendorong Pertumbuhan Ekonomi Lokal - Fariz Al Rizky (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
This research explores the development of packaging and labeling for MSMEs products in Galengdowo Village, Wonosalam District. MSMEs play a crucial role in the economy, both as job creators and drivers of inclusive economic growth. One of the biggest challenges faced by MSMEs is product marketing, where packaging and labeling significantly contribute to attracting consumer attention, providing clear information, and distinguishing products from competitors. This study aims to explore strategies for developing packaging and labeling that enhance the attractiveness and competitiveness of MSME products. Methods used include observation and analysis of factors influencing design choices, materials, and messaging in packaging and labeling. The research findings indicate that innovation in label and packaging design, such as using visually appealing stickers with images and colors, can enhance visibility and sales of MSME products. In conclusion, effective packaging and labeling development can positively contribute to the sustainability and competitiveness of MSMEs in an increasingly competitive market.